Essential skin shrinkage: cicatricial ectropion, a histopathologic evaluation and clinical analysis. (3rd March 2020) - Culter-Peck, Carolee M.; Dryden, Stephen C.; Fowler, Brian T.; Kovacic, Dianne; Slominski, Andrzej; Fleming, James C.
ABSTRACT: Purpose : To describe common risk factors in patients with Essential Skin Shrinkage (ESS) and identify corresponding histopathologic changes in lower eyelids. Methods : A case-control study was performed after an Internal Review Board approval was obtained. Consecutive patients who underwent surgical repair for ectropion with ESS of the lower eyelid were enrolled along with 10 control patients. Informed consent was obtained on all patients. Fitzpatrick skin type, history of sun exposure and non-melanoma skin cancer was obtained along with relevant physical exam findings. Skin samples obtained during surgical repair were evaluated by light microscopy for the extent of dermal actinic change. Statistical analysis was performed. Results : Sixteen study subjects and 10 control patients were enrolled. Subjects were found to be predominantly male, older than controls (p = 0.0011) and have Fitzpatrick skin type (FST) I or II while controls had type I, II or III (p = 0.0221). Hours of sun exposure reported by subjects ranged from 23, 165 to greater than 125, 000 h, versus 1, 459 to 46, 890 h in controls (p = 0.0002). Nine of 16 (56%) subjects had a history of skin cancer compared to only 3/10 controls (30%) (p = 0.2475). Histopathologic evaluation using the Fritschi scale for dermal actinic damage identified an average grade of 3.6 for subjects and 2.4 for controls (p = 0.0095). Conclusions : ESS is predominantly seen in male individuals with FST I or II and a history of extensive sun exposure. Histopathologic evaluation shows moderate to severe actinic damage. These individuals frequently have concomitant non-melanoma skin cancer.